2005
DOI: 10.1080/08941920590959640
|View full text |Cite
|
Sign up to set email alerts
|

Community and Community Development in Resource-Based Areas: Operational Definitions Rooted in an Interactional Perspective

Abstract: An understanding of community development in resource-based areas must begin with an awareness of what a community is and how it develops. In this article I provide a conceptual foundation for operational definitions of community and community development. The proposed working definitions are grounded in sociological theory and empirical research. This endeavor is timely since so much of our social, economic, and political rhetoric makes reference to these two concepts yet fails to provide adequate interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 2 publications
4
61
1
2
Order By: Relevance
“…Moreover, people are more likely to form relationships with peers who have similar characteristics (Morry, 2007). Consequently, community is frequently defined as a group of people who share attributes (Dunning, 2009;Mcclellan, 2011;Nieckarz, 2005;Singer, 2006;Theodori, 2005). However, the findings of this study indicate that communities can also be diverse; it was reported in two out of three focus group discussions.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Moreover, people are more likely to form relationships with peers who have similar characteristics (Morry, 2007). Consequently, community is frequently defined as a group of people who share attributes (Dunning, 2009;Mcclellan, 2011;Nieckarz, 2005;Singer, 2006;Theodori, 2005). However, the findings of this study indicate that communities can also be diverse; it was reported in two out of three focus group discussions.…”
Section: Discussioncontrasting
confidence: 39%
“…Gochenour (2006) acknowledges that people are beginning to conceive the concept of territory-free communities unbounded by physical location. Recent studies define community in two ways: based on geographical location or independent of location (Hall, 2009;Rodriquez, Cobigo et al, "Understanding Community" CJDS 5.4 (December 2016) 193 2013Theodori, 2005). Virtual spaces (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Collective action and community agency is vital to protecting, retaining, and maintaining rural communities (Wilkinson, 1991;McDonagh, 2001;Moseley, 2003;Luloff and Bridger, 2003;Flora and Flora, 2003;Theodori, 2005;Brennan et al, 2005). This is particularly critical where extralocal development has threatened and eroded rural cultures and economies.…”
Section: Introductionmentioning
confidence: 97%
“…In such environments, local community agency can serve as an essential tool in the development and protection of community. Some have suggested that such collective capacities are a necessary condition for both mitigating the negative forces impacting communities and enhancing the positive factors associated with social wellbeing (Luloff and Bridger, 2003;Flora and Flora, 2003;Douglas and Chadwick, 2004;Theodori, 2005;Brennan et al, 2005;Connelly, 2006). Community agency and successful collective action consists of the purposive and concerted efforts of local residents to achieve local goals (Wilkinson, 1991;Moseley, 2003;Varley, 2003;Brennan et al, 2005;Van der Platt and Barrett, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…As residents and groups interact over issues important to all of them, what has come to be known as community agency emerges (Luloff & Bridger, 2003;Theodori, 2005). Agency reflects the building of local relationships that increase the adaptive capacity of local people within a common territory.…”
Section: Introductionmentioning
confidence: 99%